BAHASA GURU DALAM MENGEKSPRESIKAN PENGHARGAAN (REWARD) DAN HUKUMAN (PUNISHMENT) KEPADA SISWA DI TAMAN KANAK-KANAK (TK ) AISYIYAH IV KOTA BENGKULU - Asparida, Asparida (UNIB Press, 2015)
This study aims to determine the teachers' use of language in expressing appreciation and punishment in Kindergarten (TK ) Aisyiyah IV Bengkulu City. The theory is used with respect to theories of language teachers, the theory of appreciation, and the theory of punishment. The method used in this study is a qualitative descriptive method. With the source data comes from the learning activities undertaken by teachers and students in kindergarten classes B-1 and B-3 IV Aisyiyah city of Bengkulu with data in the form of language teachers in learning activities obtained from the recording. Data collection techniques using the recording techniques. Then, data analysis techniques with the following steps: (a) transcription, (b) identification, (c) reduction, (d) coding and classification, (e) interpretation, and (f) conclusion. The study suggests that teachers in TK Aisyiyah IV Bengkulu award by 28 dialog (51.85%) in Teaching and Learning Activities (KBM) in the Class B-1 from a total of 54 teachers dialog. While the teaching in the class B-3 teachers awarded the dialogue as much as 22 (30.55%) of the number of teachers is 72 dialog dialog. Both of KBM in the Class B-1 as well as teaching at the Class B-3, overall teacher award in the form of praise. Forms of teacher praise given the form of words: children pious, smart kid, smart, dear, industrious boy, the son of a quick, great kids, correct, and neat. Then, in giving punishment (punishment) there are 4 dialog teachers (0.74%) in Teaching and Learning Activities (KBM) in the Class B-1 of the overall total of 54 teachers dialog dialog. Whereas the KBM in Class B-3, the teacher punishes the dialogue as much as 13 (1.80%) of the overall dialogue sebayak 72 teacher dialogue. Punishment by teachers, both in the Class B-1 and the Class B-3 as a whole in the form of preventive punishment in the form of advice and words of command and the contents of the advice, such as the use of the phrase should not, take turns speaking, no, not a pious child, should see the teacher, should not break, should not eat, repeat attached, should not be throwing, and should not be saying nasty.